2015
DOI: 10.1104/pp.114.255216
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosylation Positively Regulates Ascorbate Peroxidase Activity during Plant Stress Responses

Abstract: Nitric oxide (NO) and reactive oxygen species (ROS) are two classes of key signaling molecules involved in various developmental processes and stress responses in plants. The burst of NO and ROS triggered by various stimuli activates downstream signaling pathways to cope with abiotic and biotic stresses. Emerging evidence suggests that the interplay of NO and ROS plays a critical role in regulating stress responses. However, the underpinning molecular mechanism remains poorly understood. Here, we show that NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(149 citation statements)
references
References 59 publications
12
137
0
Order By: Relevance
“…They illustrate that $NO and ROS signaling can underlay synergistic or antagonistic mechanisms or function in parallel. Moreover, the observations by Yang et al (2015) support the notion that $NO-based modifications of antioxidant enzymes play a key role in the regulation of oxidative stress and ROS homeostasis and provide evidence for a molecular mechanism of the sensor-effector relationship between $NO and ROS. Although the $NO research starts to focus on oxidative stress and redox signaling mediated by ROS, we will probably never be able to solve all $NO and ROS interactions, but we should and we can identify critical interfaces, such as the interaction of $NO with ascorbate peroxidase.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…They illustrate that $NO and ROS signaling can underlay synergistic or antagonistic mechanisms or function in parallel. Moreover, the observations by Yang et al (2015) support the notion that $NO-based modifications of antioxidant enzymes play a key role in the regulation of oxidative stress and ROS homeostasis and provide evidence for a molecular mechanism of the sensor-effector relationship between $NO and ROS. Although the $NO research starts to focus on oxidative stress and redox signaling mediated by ROS, we will probably never be able to solve all $NO and ROS interactions, but we should and we can identify critical interfaces, such as the interaction of $NO with ascorbate peroxidase.…”
supporting
confidence: 59%
“…The cycle involves the antioxidant metabolites: ascorbate, glutathione, and NADPH and the enzymes linking these metabolites, among them ascorbate oxidase (Noctor and Foyer, 1998). In this issue, Yang et al (2015) add a new and important aspect to the interplay of $NO and ROS metabolism and control: the regulation of the ROSdegrading enzyme ascorbate peroxidase by nitric oxide. They demonstrated that $NO positively regulates the activity of cytosolic ASCORBATE PEROXIDASE1 by S-nitrosylation of Cys-32.…”
mentioning
confidence: 99%
“…S-nitrosylation of SABP3 suppresses its binding with salicylic acid and the enzymatic activity during the hypersensitive response, whereas S-nitrosylation of FBA6 negatively regulates its enzymatic activity van der Linde et al, 2011). S-Nitrosylation of APX1 enhances its enzymatic activity in response to oxidative stresses (Yang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…6F). Transgenic plants with reduced protein levels or activities of CAT and APX revealed accumulations of H 2 O 2 , an early event in PCD (Dat et al, 2003), and cytosolic APX was found to be S-nitrosylated at the onset of PCD (de Pinto et al, 2013;Lindermayr and Durner, 2015;Yang et al, 2015). The enhanced S-nitrosylation of CAT and APX in the NE genotype upon ozone fumigation may analogically lead to increased H 2 O 2 levels compared with the IE genotype.…”
Section: Target Sites Of No Action In Ie and Ne Gray Poplarmentioning
confidence: 95%